Genomic Characterisation and Comparison of Antibiotic Resistant and Sensitive Helicobacter pylori in New Zealand - King, Zoe (Auckland University of Technology, 2021)
Helicobacter pylori is an important and prevalent human pathogen present in approximately 50 % of the world’s population; causing a range of clinical outcomes from chronic gastritis and gastric ulcers to gastric carcinoma and gastric mucosa-associated lymphoid tissue lymphoma (Hooi et al. 2017; Huang et al. 2002; Kuipers et al. 1995). Treatment of this pathogenic bacterium is becoming increasingly challenging due to the increasing levels of antibiotic resistance worldwide (Malfertheiner et al. 2017; Savoldi et al. 2018). To effectively treat this bacterium, local resistance rates must be known for clinicians to administer the appropriate antibiotics for the highest chance of eradication (Malfertheiner et al. 2017). Within New Zealand (NZ) there is a lack of data on antibiotic resistance rates and levels, as well as a lack of knowledge on the genomic mechanisms causing resistance. This study aimed to increase the understanding of the levels of antibiotic resistant strains of H. pylori in NZ, as well as elucidate the underlying mechanisms causing resistance. Five H. pylori strains (A, B, C, D, and E), provided by Middlemore Hospital (Auckland, NZ) from patients undergoing gastroscopy were subject to antibiotic susceptibility testing, phylogenetic analysis, and comparative genomic analysis to determine their resistance profiles, genomic relationships, genomic characterisations and to identify known and novel mechanisms of resistance. Antibiotic susceptibility testing was performed using two methods, in-house using disc diffusion, and by Middlemore Hospital using Epsilometer test (E-test) strips. In-house testing was unsuccessful. Results obtained from Middlemore Hospital were used to determine the resistance profiles of each isolates. Each isolate was tested against commonly used antibiotics in treatment of H. pylori infections clarithromycin, metronidazole, amoxicillin, and tetracycline. One isolate (A), was sensitive to all antibiotics tested, two isolates (B and E), were resistant to clarithromycin and metronidazole at > 256 μg/mL each, and two isolates (C and D), were resistant to only clarithromycin at 24 μg/mL and 1 μg/mL, respectively. Isolate D did not survive the experimental process and was not investigated further. Sanger sequencing was initially used to sequence the 16S rRNA region to provide preliminary sequence-based identification of the four remaining isolates (A-C and E). Phylogenetic analysis was completed using the 16S rRNA gene, MLST genes, and PhyloPhlAn2 (400 genes) extracted from Illumina based sequencing of each isolate (A-C and E). The relationships of the isolates (A-C and E) were assessed with a dataset of 155 complete H. pylori genomes. The 16S rRNA gene and MLST genes highlighted the genomic diversity of the H. pylori species and identified each isolate (A-C and E) as separate strains, likely arising from different sources. Also using the draft genomes, a phylogenetic analysis using PhyloPhlAn2 was employed using which increased the resolution of the trees but still lacked enough sequence information to decipher the interspecies relationships of the dataset. However, the closest relatives to each isolate (A-C and E) were identified from this dataset using the nucleotide sequence PhyloPhlAn2 tree and used for further analysis. The draft genomes of isolates A-C, and E, were also used for comparative genomics with their respective closest references. Characterisation of the genomes showed similar characteristics to other H. pylori isolates. Comparison of the genomes to identify known mechanisms of resistance showed that the A2147G mutation within domain V of the 23S rRNA gene, conferring clarithromycin resistance, was only present in isolates B and C. The R16H amino acid substitution within RdxA, suggested to be involved with metronidazole resistance, was only identified in isolate B. Efflux pumps HefABC, HP1181, and HP1184 were identified in all isolates (A-C and E) and may be a common mechanism of resistance amongst all isolates, however, further work is required to establish their role in antibiotic resistance. The search for novel resistance mechanisms using CARD and OrthoVenn2 identified a major facilitator superfamily (MFS) efflux protein and an outer membrane protein (OMP) identified only in resistant isolates (B, C, and E), which are of further interest to elucidate their potential involvement in antibiotic resistance. Overall, these results suggest that both clarithromycin and metronidazole resistance are present in NZ H. pylori strains. Antibiotic resistance appears to develop independently and through different methods based on the phylogenetic methods employed in this study. None of the resistant isolates (B, C, and E) shared one common mechanism of resistance, however, the presence of efflux pumps, in both sensitive (A) and resistant (B, C, and E) strains, suggests that this mechanism may play an important role in resistance. More work is required to fully elucidate the role of efflux pumps and the two novel proteins in antibiotic resistant H. pylori.
Keywords: New Zealand; Helicobacter pylori; Antibiotic resistance; Comparative genomics; Clarithromycin; Metronidazole; Amoxicillin; Tetracycline